Wastewater-based monitoring reveals geospatial-temporal trends for antibiotic-resistant pathogens in a large urban community. (15th May 2023) - Rahman, Zillur; Liu, Weijia; Stapleton, Lara; Kenters, Nikki; Rasmika Dewi, Dewa A.P.; Gudes, Ori; Ziochos, Helen; Khan, Stuart J.; Power, Kaye; McLaws, Mary-Louise; Thomas, Torsten
Abstract: Antimicrobial resistance (AMR) is one of the top ten global health threats, and current surveillance programs rarely monitor it outside healthcare settings. This limits our ability to understand and manage the spread of AMR. Wastewater testing has the potential to simply, reliably and continuously survey trends in AMR outside the healthcare settings, as it captures biological material from the entire community. To establish and evaluate such a surveillance, we monitored wastewater for four clinically significant pathogens across the urban area of Greater Sydney, Australia. Untreated wastewater from 25 wastewater treatment plants (WWTPs) covering distinct catchment regions of 5.2 million residents was sampled between 2017 and 2019. Isolates for extended-spectrum β-lactamases-producing Enterobacteriaceae (ESBL-E) were consistently detected, suggesting its endemicity in the community. Isolates for carbapenem-resistant Enterobacteriaceae (CRE), vancomycin-resistant enterococci (VRE), and methicillin-resistant Staphylococcus aureus (MRSA) were only occasionally detected. The flow normalized relative (FNR) ESBL-E load was positively correlated with the proportion of the population between 19 and 50 years of age, completion of vocational education and the average length of hospital stay. Collectively, these variables explained only a third of the variance of the FNR ESBL-E load, indicating further, yet-unidentified factors as a contributor to the distribution. About half of the variation in the FNR CRE load was explained by the average length of hospital stay, showing healthcare-related drivers. Interestingly, variation in the FNR VRE load was not correlated to healthcare-related parameters but to the number of schools per 10, 000 population. Our study provides insight into how routine wastewater surveillance can be used to understand the factors driving the distribution of AMR in an urban community. Such information can help to manage and mitigate the emergence and spread of AMR in important human pathogens. Graphical abstract: Image 1 Highlights: Wastewater testing revealed geospatial-temporal trends of resistant pathogens. Extended-spectrum β-lactamases-producing Enterobacteriaceae was endemic in Sydney. Healthcare-related factors did not strongly influence resistant pathogens load. Wastewater testing can monitor resistant pathogen distribution in the community.